Analisis Kinerja Ruas Jalan Raya Ranau Akibat Kegiatan Komersial Kawasan Terminal Muaradua (Studi Kasus : Kota Muaradua - Kabupaten OKU Selatan) - Willy Agus (Jurnal Teknik Sipil, 2012)
Besides resulting positive impact, the comercial area of Muaradua terminal also results in negative impacts. The positive impact that comes from Muaradua terminal provides parking areas around the areas, while the negative impact is the Muaradua has economic value attraction resulting in more traffic jam in Jl. Ranau. This congestion will couse problems, so that requires further analysis to anticipate the increasing of traffic in the next year. The result of study indicate that Jl. Ranau is on the level B (the traffic is stable, and there is a possibility of delay). With 13 % increasing growth of vehicles, in 2012 the service level of ”Ranau” highway would be V/C = 0.89 or LOS = D. It means that if there is no increasing highway capacity or the increasing lay out of areas around the highway, there would be sever traffic jams around the highway area.